(3GdSdhc GdGSJgdGcj ddSGFM aj VhA hGbY GdOhd GdeJbOeI hGdOhd GdfGejI (B:s (3OQGSI aj GdCfKQhHhdhLjG GdGbJUGOjI (B/s - (3OYHS, eMeO jSQj GHQGgjes ((3GdGScfOQjI(B: s (3GdHjWGT SfJQ ddfTQ h GdJhRjY(B, s, 2002)
(3GdeaGgje hGdJUhQGJ hGdGJLGgGJ GdfXQjI Mhd GdSjGMI hGdSGFM hhbJ GdaQGZ hGdESJgdGc(B-(3GdeSdc GdSjGMj(B((3GdSeGJ hGdNUGFU hGdOhGaY hGdMbhb hGdhGLHGJ hGdYhGed GdeNJdaI GdeDKQI(B)-(3GdYhGed GdeNJdaI GdeDKQI aj CfeGW GdGSJgdGc eY GdJWHjb aj GdeLGd GdSjGMj,CfeGW GdSjGMI hCfhGYgG GdeNJdaI heYOdGJ GdGfaGb hGdGSJgdGc(B-(3MeGjI GdeSJgdc GdSjGMjs
(3GdghGeT U(B.307 (3agQS GdLOGhd U(B.317 (3agQS GdCTcGd U(B.317s
Keywords: (3GdSjGMI(B- (3GbJUGOjGJs; (3GdeSJgdchfs